Adsorption of Sodium dodecylbenzene sulfonate (DBS) by c-3,4-di-methoxyphenylcalix [4]resorcinarene triphenylphosphonium chloride - Rika Wulandari; Dwi Siswanta (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2018)
Surfactants have been widely used in many industries, one of them is sodium dodecylbenzene sulfonate (DBS) which is a major component used in the manufacture of detergents and considered as toxic material. Various methods have been undertaken to reduce DBS content in water. One of them is adsorption, which is known as the most effective and environmentally friendly method so far. Our previous study has successfully synthesized an adsorbent C–3,4–dimethoxyphenylcalix[4]resorcinarene triphenylphosphonium chloride (CRP). The aim of this study is to investigate the adsorption of DBS by CRP. Adsorption studies were carried out using the batch methods at different acidity, contact time, and initial DBS concentration and analyzed using UV–Visible, FTIR, and SEM–EDX spectrophotometer. The results showed the optimum condition of DBS adsorption was at pH 8, contact time 120 min, and DBS concentration 40 mg/L. The maximum capacity for the adsorption process was 12.93 mg/g. The rate of adsorption was found to follow the pseudo second–order kinetic model and the Langmuir adsorption isotherm. The mechanism was a chemisorption that occur in monolayer (G ads = –24.87 kJ/mol).